Meningkatkan Potensi Wisata Desa Jeruk Manis, Kecamatan Sikur, Kabupaten Lombok Timur - Suripto; Inayatullah; Nia Maulida (Universitas Mataram, 2023)
Tourism is a journey carried out by a person or group of people who visit certain places for the purpose of recreation, personal development or to study the unique attractiveness of a tourist spot. Jeruk Manis Village, is a tourist village that presents a natural panorama in the form of a waterfall as the main spot to attract tourists. The waterfall in Jeruk Manis village has the potential to be known throughout the archipelago because apart from its beautiful views, its location or location is hidden and not known to many people. Several tourist objects in Jeruk Manis village include the Durian Indah, Sarang Walet and Tibu Bunter waterfalls. Around each waterfall tourism object, several tour packages can be offered, such as soft tracking, observation of flora, especially medicinal plants and bird's nest ferns, and observation of fauna in the form of Celepuk Rinjani langurs. Another type of tourism object developed by the community is a hill decorated with flowering plants with views of the surrounding rice fields, which is known as the Flower Hill. Apart from tourism, Jeruk Manis village is unique in terms of rice fields with a structure in the form of terraced or terraced rice fields which have great potential in the field of agro-tourism. The tourism potential in question includes tourism to cross-breed vanilla flowers, grow vegetables, flowering plants and fruit trees. These natural resources in the form of waterfalls, flower hills and terraced rice fields in Jeruk Manis village are what support and become the initial capital for the development of a tourist village.